Effects of parboiling treatment on the edible qualities, gelatinization properties and in vitro digestive properties of brown rice and white rice - ZHAO Kangcheng; TAN Bin; LI Sen; WU Nana (浙江大学学报. 农业与生命科学版)
The edible qualities, gelatinization properties and in vitro digestive properties of brown rice, white rice, parboiled brown rice and parboiled white rice were studied. The results showed that the whiteness of parboiled brown rice and parboiled white rice was lower than that of brown rice and white rice, respectively. The taste value (including the taste value of cooked rice and the taste value of raw rice) of parboiled brown rice and parboiled white rice was lower than that of brown rice and white rice, respectively. The taste value of cooked rice of parboiled white rice was 70.95±3.72, which was significantly higher than that of parboiled brown rice (36.13±1.53, P＜0.05). The gelatinization enthalpy of parboiled brown rice and parboiled white rice [(1.39±0.08) J/g and (1.32±0.04) J/g, respectively] was significantly lower than that of brown rice and white rice [(5.62±0.99) J/g and (8.32±0.17) J/g, respectively]. The in vitro digestibilities of parboiled brown rice and parboiled white rice at 240 minutes were (57.01±0.78)% and (60.23±0.35)%, respectively, while the in vitro digestibilities of brown rice and white rice at 240 minutes were (61.90±0.64)% and (66.10±0.16)%, respectively. The whiteness, taste value of cooked rice and gelatinization enthalpy of parboiled brown rice after parboiling treatment were significantly reduced compared with those of brown rice. In addition, the in vitro digestibility, rapidly digestible starch (RDS) content and glycemic index (GI) of parboiled brown rice were decreased, while the slowly digestible starch (SDS) and resistant starch (RS) contents of parboiled brown rice were increased compared with those of brown rice. The whiteness, taste value of cooked rice and gelatinization enthalpy of parboiled white rice after parboiling treatment were significantly reduced compared with those of white rice. The in vitro digestibility, RDS content and GI of parboiled rice were reduced, while the SDS and RS contents of parboiled white rice were increased compared with those of white rice. This study may provide a basis for the research and development of nutritious and healthy rice products.